Good budgeting practices in Malaysian public universities - Tayib, Mahamad; Amir Hussin, Mohamad Rosni (Earlybrave publication, 2003)
Management accounting literature has put forward the characteristics of good budgeting practices by the private sector. This study, therefore, attempts to explore whether those characteristics were also adopted by the public sector agencies. Eight public universities were selected in the study.The findings indicate that Malaysian public universities do adopt some of these characteristics.Further research needs to be carried out in order to measure the quality of budgeting systems actually practised in public universities as this study only focuses on the characteristics of good budgeting systems.